Analysis of Multi-Hop Strategies in LEACH Protocol - Pinheiro, Diego; Garça, Juliana; de Lima, Otávio; Furtado Júnior, Corneli (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2019: Anais do IX Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2019)
Although promising, wireless sensor networks (WSNs) still have energetic limitations to overcome. One of the most used techniques to overcome these limitations is clustering. Clustering protocols like LEACH are capable of reducing communication costs by exploring data aggregation inside clusters. Another primary technique is multi-hop routing, which is a very efficient way to relay packets in the network. We evaluate different multi-hop strategies in LEACH networks. The experiments evaluate the networks for a large variety of parameters like area, packets size, the number of frames, among others. We measure the network lifetime as a performance indicator. The results point out that intra-cluster multi-hop is the most suitable option for most of the network configurations.